Effects of heat input on the mechanical properties of butt-welded high and ultra-high strength steels. (1st November 2019) - Amraei, Mohsen; Ahola, Antti; Afkhami, Shahriar; Björk, Timo; Heidarpour, Amin; Zhao, Xiao-Ling
Highlights: Studied the effect of heat input on the mechanical properties welded high strength steel. S700, S960 and S1100 steel plates were butt welded using GMAW and laser welding. Micro-hardness measurements were performed at the through-thickness of weldments. Microstructure of the weldments were examined especially at the heat affected zone. Abstract: In this study, the mechanical properties of butt-welded thin plates made of S700, S960 and S1100 steels under various heat inputs (HI) are investigated. The gas metal arc welding (GMAW) process with two different levels of HI, and laser welding (LW) are implemented for this purpose. Fully automated welding process is employed to attain high quality and homogeneous weldments. Standard tensile tests of the butt-welded joints, together with micro-hardness measurements are conducted in this study. The microstructure of the heat affected zones (HAZ) of the weldments are closely examined using scanning electron microscopy (SEM). It was observed that while the fracture was occurred at the base materials of all S700 and S1100 weldments, the S960 suffered from failure at the HAZ which resulted in reduction of the joint's strength and ductility. For all the studied steels, it was found that the joint's ductility is highly dependent on HI values over the range of 0.3–1.4 kJ/mm for each welding pass. Though, the S1100 steel showed the best performance under welding HI with a moderate change in its mechanical properties and a stable microstructure after welding compared to S700 and S960.